Review of Rural Marketing in India and Innovations in Rural Marketing - Bhavika Pandita Hakhroo (International Journal of Engineering and Management Research, 2020)
The aim of this research is to study the current scenario of Rural Marketing in India, the rural market presents with its various opportunities and challenges, given how diversely populated the rural consumers in India are. The rural market consists of 83.3 crore people and this is what attracts marketers to enter in this market. To market in the territory of rural marketing corporations must understand the rural consumer. There is a shift incoming from urban to the rural marketing as the development and levels of literacy and awareness among the rural consumers is rising and these consumers want value for their money. Marketers when catering to rural consumers need to connect with them and also undertake demonstrations for the better understanding of the rural people. Many innovations in the strategy to market into the rural markets have been undertaken in the past years. This paper aims to understand these innovations and strategies and to understand the rural consumer of India. The future of rural marketing and the development in rural areas is promising in development of rural economies and for the people living in these rural areas a better life.